Dystrophin-deficient cardiomyocytes derived from human urine: New biologic reagents for drug discovery - Xuan Guan; David L. Mack; Claudia M. Moreno; Jennifer L. Strande; Julie Mathieu; Yingai Shi; Chad D. Markert; Zejing Wang; Guihua Liu; Michael W. Lawlor; Emily C. Moorefield; Tara N. Jones; et al. (Stem Cell Research, 2014)
The ability to extract somatic cells from a patient and reprogram them to pluripotency opens up new possibilities for personalized medicine. Induced pluripotent stem cells (iPSCs) have been employed to generate beating cardiomyocytes from a patient's skin or blood cells. Here, iPSC methods were used to generate cardiomyocytes starting from the urine of a patient with Duchenne muscular dystrophy (DMD). Urine was chosen as a starting material because it contains adult stem cells called urine-derived stem cells (USCs). USCs express the canonical reprogramming factors c-myc and klf4, and possess high telomerase activity. Pluripotency of urine-derived iPSC clones was confirmed by immunocytochemistry, RT-PCR and teratoma formation. Urine-derived iPSC clones generated from healthy volunteers and a DMD patient were differentiated into beating cardiomyocytes using a series of small molecules in monolayer culture. Results indicate that cardiomyocytes retain the DMD patient's dystrophin mutation. Physiological assays suggest that dystrophin-deficient cardiomyocytes possess phenotypic differences from normal cardiomyocytes. These results demonstrate the feasibility of generating cardiomyocytes from a urine sample and that urine-derived cardiomyocytes retain characteristic features that might be further exploited for mechanistic studies and drug discovery.